The Major G-Quadruplex Formed in the Human Platelet-Derived Growth Factor Receptor β (PDGFR-β) Promoter Adopts a Novel Broken-Strand Structure in K(+) Solution - Chen, Yuwei (2012)
Overexpression of PDGFR-β has been associated with cancers, vascular and fibrotic disorders. PDGFR-β has become an attractive target for the treatment of cancers and fibrotic disorders. DNA G-quadruplexes formed in GC-rich nuclease hypersensitivity element (NHE) of the human PDGFR-β gene promoter has been found to inhibit PDGFR-β transcriptional activity. Here we determined the major G-quadruplex formed in the PDGFR-β promoter. Instead of using the four continuous runs with three or more guanines, this G-quadruplex adopt a novel folding with a broken G-strand, to form a primarily parallel-stranded intramolecular structure with three 1-nt double-chain-reversal loops and one additional lateral loop. The novel folding of the PDGFR-β promoter G-quadruplex emphasizes the robustness of parallel-stranded structural motifs with a 1-nt loop. Together with recent progress on G-quadruplexes formed in gene promoter sequences, the 1-nt-looped G(i)NG(j) motif may be evolutionarily selected to serve as a stable foundation for the promoter G-quadruplexes to build upon. The novel folding of the PDGFR-β promoter G-quadruplex may represent an attractive target for small molecule drugs that specifically target this secondary structure and modulate PDGFR-β gene expression.